Analysis of the speed of light in the vacuum of a resistant medium - Monroy, Oscar (2022)
The propagation of light is studied as a mechanism for the transmission of organized information through the underlying void of a resistant homogeneous medium. A substrate compatible with the inherent kinematic viscosity of the medium is constructed, which is defined by a system of parametric equations compatible with the properties of the medium. As a consequence, an equation is obtained for the speed of light that varies with time for a given magnitude of the local vector quantum associated with the resistant medium. The equation obtained indicates the transmission of organized information in the medium and shows a double direction that would be correlated with the opposite vector quanta. These vector quanta would not be exactly opposite and would exhibit excess and defect fluctuations reciprocally. Thus, for quasi-equilibrium states of the natural system, the fluctuations of the vector quanta would be small with respect to the magnitude of the representative vector quantum, and for disequilibrium states the fluctuations would be large or comparable with respect to the magnitude of the representative vector quantum. The results are used to study the functioning of the intracellular virion, and it is deduced that for each viral particle there would be a viral antiparticle with opposite properties in its nucleic acid. Finally, a reduced equation for the speed of light is obtained that describes the replication speed of the viral particle as a function of the number of steps in the conical nucleic acid spiral and the light absorption coefficient.